Self-Targeted Subsidies : The Distributional Impact of the Egyptian Food Subsidy System - Adams, Richard H. Jr. (World Bank, Washington, DC, 2015)
The Egyptian food subsidy system is an untargeted system that is essentially open to all Egyptians. For this reason, the budgetary costs of this system have been high, and the ability of this system to improve the welfare status of the poor has been questioned. Since the food riots of 1977, Egyptian policymakers have been reluctant to make large changes in their food subsidy system. Rather, their strategy has been to reduce the costs, and coverage of this system gradually. For example, since 1980 policymakers have reduced the number of subsidized foods from 20 to just four. Despite these cutbacks, the author uses new 1997 household survey data to show that the Egyptian food subsidy system is self-targeted to the poor, because it subsidizes inferior goods. In urban Egypt, for instance, the main subsidized food - coarse baladi bread - is consumed more by the poor (the lowest quintile group of the population) than by the rich (the highest quintile). So subsidizing baladi bread is a good way of improving the welfare status of the urban poor. Bur in rural Egypt, where the poor do not consume so much baladi bread, the poor receive less in income transfers than the rich. In many countries, administrative targeting of food subsidies can do a better job of targeting the poor than self-targeting systems. In Jamaica, for example, poor people get food stamps at health clinics, so the Jamaican poor receive double the income transfers from food subsidies than the Egyptian poor receive. Bur starting a comparable system in Egypt, would be costly both in financial, and political terms, because many non-poor households currently receiving food subsidies would have to be excluded. For these reasons, it is likely that the government will continue to refine the present food subsidy system, perhaps by eliminating current subsidies on sugar or edible oil. Neither of these foods is an inferior good, so eliminating these subsidies will have only a minimal impact on the welfare status of the poor.